IMPLEMENTASI LEAN HEALTHCARE UNTUK MENGIDENTIFIKASI DAN MEMINIMASI WASTE DI INSTALASI RAWAT JALAN RSAI BANDUNG - Lisye Fitria; Berliana Annisa Dery; Hendro Prassetiyo (Spektrum Industri, 2019)
Lean healthcare is one way to identify and minimize waste in every service process at the outpatient installation of Al Islam Bandung Hospital (RSAI). Patients must wait more than 2 hours to get service. The tools used for the implementation of lean healthcare are current state mapping, value assessment, and Failure Modes and Effects Analysis (FMEA). The results showed that the wastage waiting category was a critical waste. Proposed improvements are expected to reduce waiting time for general patient services 65.438%, BPJS Health patients 70.632%, and contracting patients 70.921%.